1993
DOI: 10.1103/physreva.47.201
|View full text |Cite
|
Sign up to set email alerts
|

Distorted-wave models for single-electron capture from molecular targets by the impact of bare ions

Abstract: Electron capture from diatomic molecular targets by the impact of bare ions is studied at high collision velocities. Different distorted-wave models, which take account of the long-range Coulombic behavior of perturbative potentials, are introduced here. Impact-parameter probabilities and singledifferential cross sections, depending on the alignment of the intermolecular axis, are studied for H++H&+ collisions. Interference patterns characteristic of scattering from the two molecular centers associated with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
5
23
0
Order By: Relevance
“…They suggested that the incoming projectile wave scatters from both atomic centers producing an interference pattern for the outgoing waves. They found that the cross section of electron transfer from hydrogen molecules into fast protons can be described by a scattering amplitude which is the coherent sum of two transition amplitudes corresponding to the atomic centers (see [4][5][6][7][8] for later work following this idea).The double slit analogy suggests that the axis of the molecule which forms the double slit has to be fixed in space to obtain interference in the scattering pattern of the projectile. The above theoretical work and subsequent experimental work, however, showed that other global observables show traces of this interference [9][10][11][12][13].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…They suggested that the incoming projectile wave scatters from both atomic centers producing an interference pattern for the outgoing waves. They found that the cross section of electron transfer from hydrogen molecules into fast protons can be described by a scattering amplitude which is the coherent sum of two transition amplitudes corresponding to the atomic centers (see [4][5][6][7][8] for later work following this idea).The double slit analogy suggests that the axis of the molecule which forms the double slit has to be fixed in space to obtain interference in the scattering pattern of the projectile. The above theoretical work and subsequent experimental work, however, showed that other global observables show traces of this interference [9][10][11][12][13].…”
mentioning
confidence: 97%
“…They suggested that the incoming projectile wave scatters from both atomic centers producing an interference pattern for the outgoing waves. They found that the cross section of electron transfer from hydrogen molecules into fast protons can be described by a scattering amplitude which is the coherent sum of two transition amplitudes corresponding to the atomic centers (see [4][5][6][7][8] for later work following this idea).…”
mentioning
confidence: 97%
“…Figure 4 of ref. [14] shows the differential cross section for electron capture dσ/d(cos ϑ) as a function of ϑ at a collision energy of 100 keV for H + -H + 2 collisions. We have integrated the curves plotted and the results are shown in Figure 5(a).…”
Section: Resultsmentioning
confidence: 99%
“…A recent brief review about the latest developments in this field is given by Schippers [8], and some even more recent experimental and theoretical works can be found in [9]. Less attention has been paid to processes which involve more than one target nucleus: some studies of collisions between H2 and bare ions are reported, for example, in [8,[10][11][12][13], and the scattering H + -H + 2 is the subject of [14]. Calculations on these systems using quantum mechanics is far from being straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…More elaborated perturbative theoretical models which consider the inclusion of the long-range behavior of the electron-nuclei interactions have recently been developed [18]. As we are interested in the evaluation of the inhuence of the interactions between the projectile nucleus and the molecular nuclei on double-differential cross sections, just for simplicity we work in the OBK approximation.…”
Section: Introductionmentioning
confidence: 99%